KAJIAN EKOLOGIS TERHADAP PEMBANGKIT LISTRIK TENAGA PANAS BUMI DI BEDUGUL, KECAMATAN BATURITI KABUPATEN TABANAN - I G. B. Wijaya Kusuma (Environmental Research Center (PPLH) of Udayana University)
Geothermal is one of renewable energy that can be used in electric power plant.Although categorized as safe to the environment, but some parameter should be considered ifwant to develop as power plant in a big scale. Some aspects should be considered are steamcontains and physical characteristic of the steam in the reservoir and the pressure drop in theground reservoir while using geothermal. If all parameters could be full filled, thegeothermal energy can be used as electrical power plant without any complaint.